SAHABI EURYGNATHOHIPPUS FEIBELI: ITS SYSTEMATIC, STRATIGRAPHIC, CHRONOLOGIC AND BIOGEOGRAPHIC CONTEXTS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Sahabi, Libya is an important latest Miocene locality having yielded an extensive paleobotanical and vertebrate fauna. Amongst the fossil mammals there occurs an extensive, species diverse record of hipparionine horses. We develop here a complete record of Sahabi Eurygnathohippus feibeli now based on dental and postcranial material, in comparison to other equids from late Miocene equids from Europe, West Asia and Africa. We find that E. feibeli is the earliest recognized species of the predominantly African clade Eurygnathohippus, that its biogeographic range was Kenya, Ethiopia, Libya and Morocco, it ranged between 7.0 and 5.7 Ma and that it had deep-time evolutionary roots extending back to first occurring Old World hipparions. We further find that Eurygnathohippus was restricted to Africa until a more advanced member of the clade extended its range into the Indian Subcontinent during the late Pliocene, ca. 3.6-2.6 Ma.
Keywords: Eurygnathohippus feibeli; Origins; Paleobiogeographic history; Africa; late Miocene.